Injury in Pencak Silat Teenage Competitive Category Athletes at the Special Sports Class in Central Java - Purnomo, Edi; Hidayat, Afif Khoirul; Santoso, Rahmawan (JUMORA: Jurnal Moderasi Olahraga, 2024)
This research aims to identify the patterns, types, and nature of injuries experienced by teenage Pencak Silat athletes in the competitive category from the Special Sports Class in Central Java Province. The method applied in this research is quantitative descriptive with a survey technique using questionnaires and interviews. The subjects of this research are 30 teenage Pencak Silat athletes from the Special Sports Class in Central Java Province who meet the criteria of having trained in Pencak Silat for a minimum of 5 years and having participated in Pencak Silat competitions at the district, provincial, and national levels. The data analysis technique used in this research is the qualitative frequency and percentage analysis conducted using Microsoft Excel software. The results show that all teenage Pencak Silat athletes in the competitive category from the Special Sports Class in Central Java Province have experienced injuries, with the details as follows: head injuries account for 9.26%, body injuries for 4.63%, hand injuries for 46.30%, and leg injuries for 39.81%. Based on this data, it is also evident that hand injuries are the most common among teenage Pencak Silat athletes in the competitive category from the Special Sports Class in Central Java Province, followed by leg injuries, head injuries, and the least common are body injuries